Investigating Cultural Competence in English-Arabic Translator Training Programs - Bahumaid, Showqi (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2010)
This empirical study investigates the level of translation competence in English-Arabic translation among postgraduate translator trainees in the American University of Sharjah and the University of Sharjah in the United Arab Emirates. It specifically examines the trainees’ competence in rendering from English into Arabic a carefully selected sample of fifteen culture-specific expressions used in contextualized sentences, as well as the trainees’ awareness of the translation procedures employed in their renditions. The results have revealed the informants’ rather low performance in the renditions of culture-bound expressions from English into Arabic; their major types of errors involved incorrect meaning, under-translation and omission. The errors have been mainly attributed to the informants’ inadequate knowledge of English culture, their lack of awareness of the significance of the translation brief while translating, and their inappropriate use of dictionaries. Further, the informants’ improper knowledge of the translation procedures employed in rendering culture-specific expressions has been evidenced. The paper ends by offering some suggestions for developing cultural competence in postgraduate English-Arabic translator training programmes.